Evaluation of different recruitment methods: Longitudinal, web-based, pan-European physical activity through sustainable transport approaches (PASTA) project - Gaupp-Berghausen,M; Raser,E; Anaya-Boig,E; Avila-Palencia,I; de,Nazelle A; Dons,E; Franzen,H; Gerike,R; Goetschi,T; Iacorossi,F; Hossinger,R; Nieuwenhuijsen,M; et al. (Journal of Medical Internet Research, 2019)
Background:Sufficient sample size and minimal sample bias are core requirements in empirical data analyses. Combining opportunistic recruitment with an online survey and data collection platform yields new benefits compared to traditional recruitment approaches.Objective:The objective of this paper is to report on the success of different recruitment methods to obtain participants’ characteristics, participation behavior, recruitment rates, and representativeness of the sample.Methods:A longitudinal online survey was implemented as part of the European PASTA project, which was online between November 2014 and December 2016. During this period participants in seven European cities were recruited on a rolling basis. For all cities to reach a sufficient number of adult participants a standardized guide on recruitment strategy was developed. In order to make use of the strengths and to minimize weakness a combination of different opportunistic recruitment methods was applied. In addition, the city of Oerebro applied random sampling approach. In order to reduce attrition rate and improve real-time monitoring the online platform featured a participant and a researchers` user interface and dashboard.Results:A total of 10,691 participants were recruited. Most people found out about the survey through their workplace or employer (21.5 %), outreach promotion (20.8 %), and social media (17.4 %). The average number of questionnaires filled-in per participant varied between the cities, with the highest number in Zurich (11.0 ± 0.33) and the lowest in Oerebro (4.8 ± 0.17). Collaboration with local organizations, the use of Facebook and mailing lists, and direct street recruitment were the most effective approaches in reaching a high share of participants (p = <.001). Under consideration of invested working hours Facebook (p = <.001) was one of the most time-efficient methods. Compared to the cities census data, the composition